1988
DOI: 10.1128/aac.32.9.1379
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and cloning of a plasmid-borne gene encoding a phosphotransferase that confers high-level amikacin resistance in enteric bacilli

Abstract: Clinical isolates of Klebsiella pneumoniae and Serratia marcescens at a hospital that had used amikacin as its principal aminoglycoside for the preceding 42 months demonstrated high-level resistance to amikacin (greater than or equal to 256 micrograms/ml), kanamycin (greater than or equal to 256 micrograms/ml), gentamicin (greater than or equal to 64 micrograms/ml), netilmicin (64 micrograms/ml), and tobramycin (greater than or equal to 16 micrograms/ml). The resistant strains contained an identical 6.8-kiloba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Substrate activity profiling showed that the same enzyme was present in all of the amikacin-resistant isolates collected in 1984. In particular, the data differentiated between AAC(6')-I and novel forms of APH(3') that confer resistance to amikacin but not to tobramycin and netilmicin (9,16,17) as well as between AAC(6')-I and a recently described ANT(4')-II enzyme that confers resistance to amikacin and tobramycin but not to netilmicin (14). The plasmid pBWH300 was found in 12 isolates from six bacterial species (Table 4 Characterization of the amikacin resistance plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Substrate activity profiling showed that the same enzyme was present in all of the amikacin-resistant isolates collected in 1984. In particular, the data differentiated between AAC(6')-I and novel forms of APH(3') that confer resistance to amikacin but not to tobramycin and netilmicin (9,16,17) as well as between AAC(6')-I and a recently described ANT(4')-II enzyme that confers resistance to amikacin and tobramycin but not to netilmicin (14). The plasmid pBWH300 was found in 12 isolates from six bacterial species (Table 4 Characterization of the amikacin resistance plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Nontransferable (i.e., chromosomally specified) AAC(6') production by Serratia strains resulting in amikacin resistance without concomitant gentamicin resistance has also been reported (10). Recently, two other aminoglycoside-modifying enzymes, 4'-aminoglycoside nucleotidyltransferase and a 3'-phosphotransferase, have been reported to result in resistance to amikacin without concomitant resistance to gentamicin (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ANT(4')-II described here, P. aeruginosa strains were isolated that produced a phosphotransferase that was active on amikacin and an acetyltransferase that was active on netilmicin and other aminoglycosides (unpublished data). At other institutions, substitution of amikacin for alternative aminoglycosides has not generally led to an increased prevalence of resistance (2,11,29,38), but exceptions have also been reported (7,10,25,40). In Denver, the setting was especially conducive for the emergence of antibiotic resistance.…”
mentioning
confidence: 99%
“…In P. aeruginosa and other gram-negative pathogens, enzymes conferring resistance to amikacin have included several varieties of 6'-aminoglycoside acetyltransferase (16,18,19,37), 3-aminoglycoside acetyltransferase V (5,21), and certain 3'-aminoglycoside phosphotransferases (10,22). Other 3'-aminoglycoside phosphotransferases (6,30) and ANT(2")-II (4) can modify amikacin in vitro but apparently do so at slower rates, such that amikacin resistance is not augmented in vivo.…”
mentioning
confidence: 99%